2017
DOI: 10.1039/c7cc07366f
|View full text |Cite
|
Sign up to set email alerts
|

Double C–S bond formation via C–H bond functionalization: synthesis of benzothiazoles and naphtho[2,1-d]thiazoles from N-substituted arylamines and elemental sulfur

Abstract: A novel, atom economic, and environmentally friendly method for the synthesis of 2-substituted benzothiazoles and 2-substituted naphtho[2,1-d]thiazoles from N-substituted arylamines and elemental sulfur has been developed under metal-free conditions. The reaction underwent the process of double C-S bond formation through C-H bond functionalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 65 publications
3
30
0
Order By: Relevance
“…Meanwhile, in the presence of urea, catalytic current rose around 1.3 V vs. RHE as a result of UOR by Ni(OH) 2 /NiOOH redox, which was similar to OER and the previous reports. [24,25,27,29] Notably, onset potential Ni MOF for UOR was found to be at 1.34 V vs. RHE; which was closer to recent reports of NiFe LDH and Ni NP by Gao et al, b Ni(OH) 2 and Ni/Ni(OH) 2 by Singh et al, MOF-Templated Ni/C by Wang et al and higher than that of Ni MOF (BDC) by Zhu et al [27,30,42,43] On the other hand, high catalytic current density (63.15 mA cm À2 at 1.5 V vs. RHE) of Ni MOF compared to NiO WCP (8.32 mA cm À2 at 1.5 V vs. RHE) and NiO SA (30.47 mA cm À2 at 1.5 V vs. RHE) in the UOR indicates the high catalytic activity of Ni MOF towards UOR and it is found to be similar to OER catalytic activity of the present study.…”
Section: Urea Electrolysissupporting
confidence: 85%
See 1 more Smart Citation
“…Meanwhile, in the presence of urea, catalytic current rose around 1.3 V vs. RHE as a result of UOR by Ni(OH) 2 /NiOOH redox, which was similar to OER and the previous reports. [24,25,27,29] Notably, onset potential Ni MOF for UOR was found to be at 1.34 V vs. RHE; which was closer to recent reports of NiFe LDH and Ni NP by Gao et al, b Ni(OH) 2 and Ni/Ni(OH) 2 by Singh et al, MOF-Templated Ni/C by Wang et al and higher than that of Ni MOF (BDC) by Zhu et al [27,30,42,43] On the other hand, high catalytic current density (63.15 mA cm À2 at 1.5 V vs. RHE) of Ni MOF compared to NiO WCP (8.32 mA cm À2 at 1.5 V vs. RHE) and NiO SA (30.47 mA cm À2 at 1.5 V vs. RHE) in the UOR indicates the high catalytic activity of Ni MOF towards UOR and it is found to be similar to OER catalytic activity of the present study.…”
Section: Urea Electrolysissupporting
confidence: 85%
“…[41,42] Recently, Zhu et al studied Ni MOF (BDC) for UE in alkaline medium over glassy carbon (GC) and Ni foam substrate. [43] Hu et al demonstrated Ni MOF ((4,4'-bipy)(H 3 BTC); H 3 BTC = 1,3,5-Benzenetricarboxylic acid) as cathode catalyst for oxygen reduction and oxygen evolution reaction in Li-O 2 air battery. [44] Qin et al investigated Polymolybdate based MOF for HER (1,3,5-Benzene tricarboxylate) on GC substrate.…”
Section: Introductionmentioning
confidence: 99%
“…While the reactivity was found to be only slight influenced by the nature of the substituents on aromatic aldehydes, the success of the reaction depended strongly on the nature of aromatic amine substrates 220 and 221. As in the previous case, [92] 2naphthylamine 220 was proven to be more reactive than anilines 221 and its reactions could proceed at 140°C. In cases of anilines 221, despite the presence of multiple electron donating groups such as alkyl, alkoxy, their reactivity remained lower than that of 2napthylamine 220.…”
Section: Scheme 70supporting
confidence: 64%
“…In 2017, a synthesis of 2-substituted naphtho[2,1-d]thiazoles 217 via heating of the corresponding N-substituted 2-naphthylamines 215 with elemental sulfur at 140°C was reported (Scheme 72). [92] The reaction could proceed via the oxidation of the N-methylene group into the corresponding imine 216. Substrates bearing a substituent R that is aromatic, heteroaromatic, styryl, ester or benzoyl are competent substrates.…”
Section: Scheme 70mentioning
confidence: 99%
“…And it has been recognized as a powerful strategy by harnessing elemental sulfur as the sulfur source to construct S-containing compounds. [8][9][10][11][12] Inspired by considerable efforts in the preparation of S-containing compounds, [13][14][15][16][17][18] we envisioned the possibility of elemental sulfur incorporated indole and 2bromobenzylaldehyde to produce the desired thiochromeno [2,3-b]indole. Recently, we found that elemental sulfur could accelerate the reactivity of the 3-position of indoles.…”
mentioning
confidence: 99%